The impact of foot arch height on quality of life in 6-12 year olds (Colombia Medica, 2014)
Objective: To determine whether arch height affects schoolchildren's health-related quality of life.Methods: One hundred and thirteen schoolchildren attended an out-patient centre where self-reported data were recorded, their feet were classified into one of three groups according to their arch index (high, normal, or low), and the scores obtained from the Foot Health Status Questionnaire (FHSQ - Spanish version) were compared.Results: The groups with high, low and normal arch recorded lower scores in Section One for the general foot health and footwear domains and higher scores in foot pain and foot function. In Section Two they obtained lower scores in general health and higher scores in physical activity, social capacity and vigour.Conclusions: A Comparison of the scores obtained reveals that arch height has a negative impact on quality of life. Given the limited extent of available evidence in respect of the aetiology and treatment of foot diseases and deformities, these findings reveal the need to implement programmes to promote foot health and carry out further research into this commonly occurring disabling condition.